2022
DOI: 10.1021/acs.macromol.2c00496
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Dissolution and Swelling of Confined Lamellar Polymer Crystals through Exposure to Humid Air

Abstract: Using a hydrophobic–hydrophilic poly­(styrene)-b-poly­(ethylene oxide) (PS-b-PEO) diblock copolymer, we formed sandwich-like micron-sized thin platelets via crystallization in solution. These platelets consisted of a crystalline PEO lamella confined between two glassy PS layers and were deposited on a solid substrate. Using in situ optical microscopy, we followed the temporal and spatial changes in the thickness and morphology of these sandwich-like platelets induced by exposure to humid air. As water is a goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…In 60 and 70% methanol aqueous solutions, the value of n is 0.3304 and 0.2630 ( n < 0.45) for the dissolution of the CD-MOF⊃FL crystal, respectively, implying that the dissolution of the CD-MOF⊃FL crystal maintained a Fickian behavior (case I transport) governed by tiny swelling and diffusion . In 75% methanol aqueous solution, n is 0.745 (0.45 < n < 0.89), indicating that the dissolution of the CD-MOF⊃FL crystal followed a non-Fickian behavior, controlled by both diffusion and erosion. , In 80 and 95% methanol aqueous solutions, n is 1.037 and 4.927 ( n > 0.89), respectively, indicating that the dissolution of the CD-MOF⊃FL crystal exhibited a Fickian behavior (case II transport) controlled by erosion …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 60 and 70% methanol aqueous solutions, the value of n is 0.3304 and 0.2630 ( n < 0.45) for the dissolution of the CD-MOF⊃FL crystal, respectively, implying that the dissolution of the CD-MOF⊃FL crystal maintained a Fickian behavior (case I transport) governed by tiny swelling and diffusion . In 75% methanol aqueous solution, n is 0.745 (0.45 < n < 0.89), indicating that the dissolution of the CD-MOF⊃FL crystal followed a non-Fickian behavior, controlled by both diffusion and erosion. , In 80 and 95% methanol aqueous solutions, n is 1.037 and 4.927 ( n > 0.89), respectively, indicating that the dissolution of the CD-MOF⊃FL crystal exhibited a Fickian behavior (case II transport) controlled by erosion …”
Section: Resultsmentioning
confidence: 99%
“…50,52 In 80 and 95% methanol aqueous solutions, n is 1.037 and 4.927 (n > 0.89), respectively, indicating that the dissolution of the CD-MOF⊃FL crystal exhibited a Fickian behavior (case II transport) controlled by erosion. 53 Additionally, the size influence on the dissolution kinetics was studied by comparing the dissolution kinetics of 160 and 80 μm CD-MOF⊃FL crystals. It takes ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After total evaporation of solvent (evaporation time ≈ 20 min), we found that a lot of square-shaped structures had emerged on the substrate. Square-shaped platelets represent classical patterns of PEG single crystals. ,, From the changes in the corresponding gray value plots of the intensity emitted from the AIE groups, we followed the crystallization process in the thin film solution. The number density of polymers at locations close to the edge of the substrate was higher, probably due to the so-called “coffee-ring effect”, resulting in an accumulation of PEG aggregates close to the edge of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Square-shaped platelets represent classical patterns of PEG single crystals. 17,30,31 From the changes in the corresponding grey value plots of the intensity emitted from the AIE groups, we followed the crystallization process in the thin lm solution. The number density of polymers at locations close to the edge of substrate was higher, probably due to the so-called "coffee-ring effect", resulting in an accumulation of PEG aggregates close to the edge of the substrate.…”
Section: Resultsmentioning
confidence: 99%